Association of prevalence of electronic cigarette use with smoking cessation and cigarette consumption in England: a time–series analysis between 2006 and 2017. (4th December 2019) - Beard, Emma; West, Robert; Michie, Susan; Brown, Jamie
Abstract: Aims: To provide up‐to‐date estimates of how changes in the prevalence of electronic cigarette (e‐cigarette) use in England have been associated with changes in smoking cessation activities and daily cigarette consumption among smokers in England. Design: Time–series analysis of population trends. Setting: England. Participants: Participants came from the Smoking Toolkit Study, which involves repeated, cross‐sectional household surveys of individuals aged 16 years and older in England. Data were aggregated on approximately 1200 past‐year smokers each quarter (total n = 50 498) between 2007 and 2017. Measurements: Prevalence of e‐cigarette use in current smokers was used to predict (a) prevalence of quit attempts among last‐year smokers, (b) overall quit rates among last‐year smokers and (c) mean cigarette consumption per day among current smokers. Prevalence of e‐cigarette use during a quit attempt among last‐year smokers was used to predict (a) quit success rate among last‐year smokers and (b) overall quit rates among last‐year smokers. Findings: Overall quit rates increased by 0.054% [95% confidence interval (CI) = 0.032–0.076, P < 0.001] and 0.050% (95% CI = 0.031–0.069, P < 0.001) respectively for every 1% increase in the prevalence of e‐cigarette use by smokers and e‐cigarette use during a quit attempt. Quit success rates increased by 0.060% (95% CI = 0.043–0.078, P < 0.001) for every 1% increase in the prevalence of e‐cigarette use during a quit attempt. No clear evidence was found for an association between e‐cigarette use and either prevalence of quit attempt (BAdj = 0.011, 95% CI = −0.046 to 0.069, P = 0.698) or cigarette consumption (BAdj = 0.019, 95% CI = −0.043 to 0.082, P = 0.542). Conclusion: Changes in prevalence of e‐cigarette use in England have been positively associated with the overall quit rates and quit success rates but not clearly associated with the prevalence of quit attempts and mean cigarette consumption.